Graph Neural Networks for Complex Network Analysis - John, Rebecca (International Journal of Emerging Research in Engineering and Technology, 2022)
Complex networks are fundamental structures underlying numerous real-world systems, including social interactions, biological processes, transportation infrastructures, communication systems, and financial markets. Traditional machine learning techniques often struggle to model such systems effectively due to their irregular, relational, and non-Euclidean nature. Graph Neural Networks (GNNs) have emerged as a powerful deep learning paradigm designed specifically to operate on graph-structured data, enabling scalable and expressive representation learning for nodes, edges, and entire graphs. By integrating principles from graph theory and neural network architectures, GNNs provide a unified framework for capturing structural dependencies, dynamic interactions, and hierarchical patterns within complex networks. This article presents a comprehensive exploration of Graph Neural Networks for complex network analysis, examining their theoretical foundations, architectural developments, training methodologies, scalability considerations, and real-world applications across diverse domains. It further discusses challenges such as over-smoothing, interpretability, computational efficiency, and robustness, while outlining emerging research directions that aim to enhance the capability and reliability of GNN-based systems. Through detailed analysis, this work demonstrates how Graph Neural Networks are reshaping the study and application of complex networks in modern artificial intelligence.